Pengaruh Pemberian Kombinasi Pupuk Organik Padat dan Organik Cair Terhadap Porositas Tanah dan Pertumbuhan Tanaman Bayam (Amarantus tricolor L.) - Imelda Anastasia; Munifatul Izzati; Sri Widodo Agung Suedy (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
The porosity of soil is one of the parameters of soil porosity. Tanah Merah in Madura island has low fertility. This soil not good to used because the physical structure and has low nutrition. The addition of organic materials from solid and liqiud organic fertilizer can increase soil porosity and spinach growth. The research aimed to determine the effect of solid, liquid organic fertilizer, and their combination to increase porosity and spinach growth. The design of the research is completely randomized design (RAL) with a single factor with combination treatment media, control treatment with no treatment to media (P0), media were given solid organic fertilizer (P1), media were given liquid organic fertilizer (P2), and media were given combination of solid and liquid organic fertilizer (P3). Analysis of the data used Analysis of Variance ( ANOVA ) continued by DMRT test with significance level of 95%. The results of the research showed organic fertilizer given effect to the increase in porosity of the soil and plant growth, as well as the provision of combination solid and liquid organic fertilizer are the most optimal fertilizer for soil porosity and spinach growth. Keywords : Spinach, solid organic fertilizer, liquid organic fertilizer, soil porosity, spinach growth